2011
DOI: 10.1016/j.neuropsychologia.2010.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Striatal responses to negative monetary outcomes differ between temperamentally inhibited and non-inhibited adolescents

Abstract: The present study compared blood oxygen level dependent (BOLD) response in behaviorally inhibited and behaviorally non-inhibited adolescents to positive and negative feedback following their choice in a reward task. Previous data in these same subjects showed enhanced activation in striatal areas in behaviorally inhibited subjects to cues predicting gain or a loss. However, no analyses had examined responses following actual gains or losses. Relative to non-inhibited subjects, behaviorally inhibited subjects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
100
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(112 citation statements)
references
References 38 publications
9
100
3
Order By: Relevance
“…This is also consistent with the Perez-Edgar et al (2007) finding that adolescents with a history of childhood BI showed exaggerated amygdala responses to all emotion faces (not just threatening ones) when asked to rate their subjective experiences. In addition, it is supported by the finding that enhanced N2 amplitudes on both incompatible (high conflict) and compatible (low conflict) trials linked BI to indices of social and emotional maladaptation (Henderson, 2010;Lahat et al, 2014b) and that a childhood history of BI is associated with the failure to discriminate between positive and negative feedback in vmPFC activation during a monetary incentive delay task in adolescence (Helfinstein et al, 2011).…”
Section: Overgeneralized Control Modelmentioning
confidence: 85%
“…This is also consistent with the Perez-Edgar et al (2007) finding that adolescents with a history of childhood BI showed exaggerated amygdala responses to all emotion faces (not just threatening ones) when asked to rate their subjective experiences. In addition, it is supported by the finding that enhanced N2 amplitudes on both incompatible (high conflict) and compatible (low conflict) trials linked BI to indices of social and emotional maladaptation (Henderson, 2010;Lahat et al, 2014b) and that a childhood history of BI is associated with the failure to discriminate between positive and negative feedback in vmPFC activation during a monetary incentive delay task in adolescence (Helfinstein et al, 2011).…”
Section: Overgeneralized Control Modelmentioning
confidence: 85%
“…In contrast, there is also evidence that adolescents show exaggerated striatal responses in anticipation of potentially negative social feedback (Guyer, McClure-Tone, Shiffrin, Pine, & Nelson, 2009). These conflicting results may be due to confounding issues related to differences in stimuli and/or the use of secondary reinforcers (e.g., money and faces) to study negative events (Bjork, Smith, Chen, & Hommer, 2011;Helfinstein et al, 2011;Somerville et al, 2011;Geier, Terwilliger, Teslovich, Velanova, & Luna, 2010;van Leijenhorst, Zanolie, et al, 2010;Galván et al, 2006). Secondary reinforcers are commonly used in developmental studies, but this approach introduces a significant confound: Without equating subjective value or motivation, the same stimulus may elicit differential responses across development.…”
Section: Introductionmentioning
confidence: 99%
“…53 Whereas Met carriers showed a VS response modulated by feedback valence and attribution, Val/Val carriers showed a VS response insensitive to feedback attribution that led to an altered VS response to SA losses -EA losses, which is similar to our findings in de pres sed patients. Moreover, increased striatal response to performance-dependent monetary losses has been reported in healthy adolescents characterized as behaviourally inhibited, 54 a temperamental trait associated with an increased risk for anxiety disorder early in life. 55 As trait anxiety and neuroticism, known risk factors for MDD, are reportedly higher in Val/Val than in Met carriers, [56][57][58][59] these results may lead to the speculation that altered motivational salience processing of SA losses is present in populations at risk for MDD.…”
Section: J Psychiatry Neurosci 2015;40(6)mentioning
confidence: 99%
“…We have previously shown in healthy individuals that RTs in trials following SA feedback are longer than in trials following EA feedback. 34,54 This post-SA feedback slowing is a behavioural measure indicating that participants are able to differentiate feedback attribution. In the present study, we observed post-SA feedback slowing in patients and controls, strongly indicating that patients were able to accurately discriminate feedback attribution.…”
Section: Limitationsmentioning
confidence: 99%